EFFICACY OF VIRECHANA KARMA WITH TRIVRUTTADI LEHA YOGA IN THE MANAGEMENT OF TAMAKA SHVASA (BRONCHIAL ASTHMA) - Shweta G.Patil,; Anup B.Thakar, (International Journal of Ayurveda and Pharma Research, 2020)
Bronchial asthma is a highly prevalent disease and in most of the etiopathogenesis and symptomatology bronchial asthma can be co-related to that of Tamaka Shvasa. As the disease is originated from Pittasthana, Virechana Karma is indicated in the treatment of Shvasa Roga .In Charak Kalpasthana there are many Virechana Yogas are mentioned with different Kashay Kalpana. So, the present study is carried out to study efficacy of Virechana with Trivrutta in combination with other Drayas mentioned in Kalpasthana in the form of Leha Kalpana specifically indicated in Shvasa Roga. Aim: To study efficacy of Virechana karma with Trivrutta Leha Yoga in Tamaka Shvasa. Materials and Methods: Total 15 patients fulfilling the diagnostic criteria of Shvasa Roga were selected from OPD & IPD of Panchakarma Department. The Sign and symptoms mainly breathlessness, cough, ronchi were given scores depending on their severity. The patients were also assessed for Lung Function Test to determine pulmonary impairment. For the purpose of Virechana they were given Deepan Pachana with Trikatu Churna for 3 days then they were subjected to Snehapana with warm cow’s Ghee. The patients were given Abhyanga and Bashpaswedana for 4 days followed by Virechana with Trivrutta Leha Yoga and Sansarjana Krama. Follow up was done in an interval of 15 days for three times and scores were noted down before and after treatment. The scores were analyzed by using Wilcoxon Signed Rank Test for subjective parameters and Studant paired ‘t’ test for objective parameters. Result: The trial drug has shown statistically highly significant reduction in breathlessness, cough, rhonchi and significant changes in lung function tests. Conclusion: The formulation has proved its best purgative effect on bronchial Asthma and thus relives the symptoms of disease immediately. It has reduced frequency of episodes of breathlessness and severity of symptoms.